1983
DOI: 10.1002/ajmg.1320160304
|View full text |Cite
|
Sign up to set email alerts
|

A familial reciprocal translocation t(3;7) (p21.1;p13) associated with the Greig polysyndactyly‐craniofacial anomalies syndrome

Abstract: A translocation t(3;7) (p21.l;p13) segregating through four generations was found to be invariably associated with the Greig cephalopolysyndactyly syndrome (GS). High resolution chromosome analyses using G and R banding did not uncover any imbalance of the affected chromosomes, nor were the late replicating patterns changed. One girl with the GS died of medulloblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Another example is in renal cell carcinoma, where both hereditary and spontaneous varieties contain alterations specifically in the 3p14--3p21 region (2)(3)(4)(5). Other chromosome 3 rearrangements include (i) the Greig polysyndactyly craniofacial anomalies syndrome due to a 3;7 translocation, t(3;7)(p21.1;p13), and (ii) both inversions and translocations involving bands 3q21 and 3q26 in acute myelogenous leukemia with megakaryocyte hyperplasia (6,7). Because of the colocalization of oncogenes and sites of chromosomal rearrangement (8), it was of interest to precisely localize the ERBA2 gene on chromosome 3.…”
mentioning
confidence: 99%
“…Another example is in renal cell carcinoma, where both hereditary and spontaneous varieties contain alterations specifically in the 3p14--3p21 region (2)(3)(4)(5). Other chromosome 3 rearrangements include (i) the Greig polysyndactyly craniofacial anomalies syndrome due to a 3;7 translocation, t(3;7)(p21.1;p13), and (ii) both inversions and translocations involving bands 3q21 and 3q26 in acute myelogenous leukemia with megakaryocyte hyperplasia (6,7). Because of the colocalization of oncogenes and sites of chromosomal rearrangement (8), it was of interest to precisely localize the ERBA2 gene on chromosome 3.…”
mentioning
confidence: 99%
“…Subsequently severa1 authors have reported similar families McKusick, 1969. Marshall andSmith 1970;Gnamey and Farriaux, 1971;Hootnick and Holmes, 1972;Duncan et al 1979;Fryns et al, 1981;Merlob et al, 1981;Chudley and Houston, 1982;Kwee and Lindhout, 1983;Tommerup and Nielsen, 1983;Baraitser et al, 1983;Gollop and Fontes, 1985;Pelz et al, 19861. Inheritance is autosomal dominant with complete penetrance but considerable intrafamilial variability [Temtamy and McKusick, 19781.…”
Section: Introductionmentioning
confidence: 96%
“…The syndrome is characterized by preaxial polydactyly of the feet, postaxial polydactyly of the hands, syndactylies of hands and feet, and mild craniofacial abnormalities such as a slight hypertelorism and a high prominent forehead (Greig, 1926). The gene locus for GCPS has been pinpointed to human chromosome 7p13 by different translocations and deletions associated with the syndrome (Tommerup and Nielsen, 1983;Drabkin et al, 1989;Kruger et al, 1989;Pettigrew et al, 1991;Wagner et al, 1990). Using somatic cell hybrid lines from different GCPS translocation patients, we were able to localize the breakpoints to the same NotI restriction fragment (Vortkamp et al, 1991a).…”
Section: Introductionmentioning
confidence: 99%